2021
DOI: 10.3390/agriculture11121211
|View full text |Cite
|
Sign up to set email alerts
|

Quality Variation of the Moldovan Origanum vulgare L. ssp. vulgare L. and Origanum vulgare L. ssp. hirtum (Link) Ietsw. Varieties in Drought Conditions

Abstract: In this paper, we have comparatively analyzed two subspecies of Origanum vulgare (O. vulgare ssp. hirtum and O. vulgare ssp. vulgare) in climatic conditions with higher than usual temperatures from the Institute of Genetics, Physiology and Plant Protection Chisinau, Rep. Moldova. The aim of the research was to study the producing capacity, content, composition of essential oil, as well as the polyphenols content in O. vulgare varieties, their drought testing and the selection of promising cultivars. Seven O. v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In this study, selected EOs were conducted to GC-MS analysis in order to determine chemical profiles and compositions. Comparing the referenced data from the literature about chemical composition with the obtained chemical compositions of EOs in this study (Table 5, Supplementary Table S1), it could be assumed that the largest number of O. vulgare essential oil do not have the same chemical composition compared with the presented oil in this study [29][30][31][32][33][34][35][36][37]. Briefly, the most abundant compound in this oil, γ-terpinene, was not defined in other studies as the most dominant compound.…”
Section: Discussionmentioning
confidence: 84%
“…In this study, selected EOs were conducted to GC-MS analysis in order to determine chemical profiles and compositions. Comparing the referenced data from the literature about chemical composition with the obtained chemical compositions of EOs in this study (Table 5, Supplementary Table S1), it could be assumed that the largest number of O. vulgare essential oil do not have the same chemical composition compared with the presented oil in this study [29][30][31][32][33][34][35][36][37]. Briefly, the most abundant compound in this oil, γ-terpinene, was not defined in other studies as the most dominant compound.…”
Section: Discussionmentioning
confidence: 84%
“…However, the yield of essential oil ranges from 0.1 to 5% and the most common component of the essential oil of O. vulgare L. is carvacrol and thymol. This is typical for the conditions of Germany (Azizi et al, 2009), Turkey (Kordali et al, 2008), Portugal (Teixeira et al, 2013), Greece (Aligiannis et al, 2001), Montenegro (Stešević et al, 2018), Hungary (Veres et al, 2007), Bosnia (Stoilova et al, 2008), Croatia (Kulisic et al, 2004), Albania (Hodaj-Çeliku et al, 2017), Slovenia (Kocić-Tanackov et al, 2012), Slovakia (Kryvtsova et al, 2020), Italy (Russo et al, 1998), India (Raina and Negi, 2014), Iran (Vazirian et al, 2015;Moradi et al, 2014), Moldova (Gonceariuc et al, 2014), Chile (Simirgiotis et al, 2020), and Spain (Carrasco et al, 2016). It should be noted that even in one country there are different chemotypes, in which the oil content and the main component differ.…”
Section: Chemical Composition Of the Essential Oilmentioning
confidence: 88%
“…The long-standing use of Origanum vulgare in folk medicine is generating even more interest in the design of new pharmaceuticals. New studies have shown medicinal properties such as antimicrobial [ 13 ], antiviral, antioxidant [ 14 ], anti-inflammatory, antispasmodic [ 15 ], antiurolytic [ 16 ], antiproliferative [ 13 ], and neuroprotective [ 17 ].…”
Section: Introductionmentioning
confidence: 99%